Linkages and boundaries in private and public international law - Abou-Nigm, Verónica Ruiz; McCall-Smith, Kasey; French, Duncan (Hart Publishing, 2018)
Do private and public international law coincide in their underlying objectives when it comes to their respective contribution to the realisation of global values? How do they work together towards the consistency and efficiency of the international legal order? This edited collection sets out a vision: to serve modern society, the international legal order cannot be defined as public or private. Linkages and Boundaries focuses on the interface between private and public international law and the synergies that a joint approach brings to topical issues, such as corporate social responsibility and environmental law, as well as foundational concepts such as international jurisdiction, state sovereignty and party autonomy. The book showcases the dynamic interaction between the two disciplines, with a view to contribute to a dialogue that is still only in the early stages of delivering its full potential. The collection explores ways to deepen the dialogue between these two distinct but interrelated disciplines, with a view to further their progression towards a more integrated and holistic approach to legal problems that require an international approach. The book brings together well-known experts and new voices from both disciplines and from a wide range of jurisdictions in Europe, North America and South America.